2021
DOI: 10.1002/eat.23579
|View full text |Cite
|
Sign up to set email alerts
|

Pilot outcomes from a multidisciplinary telehealth versus in‐person intensive outpatient program for eating disorders during versus before the Covid‐19 pandemic

Abstract: Introduction Eating disorders (EDs) are serious mental illnesses with high rates of mortality, morbidity, and personal and societal costs. Onset of the Covid‐19 pandemic led to increased ED diagnoses in the general public, as well as worsening of ED symptoms in those with an existing ED diagnosis. Heightened prevalence and severity of EDs during the pandemic is complicated by the fact that traditional modes of ED care (specialty intensive treatment provided by a multidisciplinary team) have been difficult to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 30 publications
8
46
1
Order By: Relevance
“…Although sample sizes were small (ns = 9, 25, and 93), each study found the online service to be safe, tolerated, and effective for improving general mental health and eating disorder symptoms from pre-to posttest periods. In two studies (66%), the degree of symptom improvement experienced from the online treatment was highly comparable to historical benchmarks at the same clinic (Levinson et al, 2021;Raykos et al, 2021), highlighting the viability of digitallydelivered treatments during the pandemic.…”
Section: Clinical Effects Of Online Treatmentmentioning
confidence: 73%
See 2 more Smart Citations
“…Although sample sizes were small (ns = 9, 25, and 93), each study found the online service to be safe, tolerated, and effective for improving general mental health and eating disorder symptoms from pre-to posttest periods. In two studies (66%), the degree of symptom improvement experienced from the online treatment was highly comparable to historical benchmarks at the same clinic (Levinson et al, 2021;Raykos et al, 2021), highlighting the viability of digitallydelivered treatments during the pandemic.…”
Section: Clinical Effects Of Online Treatmentmentioning
confidence: 73%
“…Three non‐randomized pilot studies evaluated the preliminary effectiveness of treatment services delivered via digital means (i.e., telehealth, videoconferencing) due to social distancing policies (Levinson et al, 2021 ; Plumley et al, 2021 ; Raykos et al, 2021 ). Although sample sizes were small ( n s = 9, 25, and 93), each study found the online service to be safe, tolerated, and effective for improving general mental health and eating disorder symptoms from pre‐ to posttest periods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these, both uncontrolled, documented promising pre-post symptom changes in small groups (n = 9 and n = 25, respectively) receiving routine treatments that were adapted to virtual formats (Plumley, Kristensen, & Jenkins, 2021;Raykos, Erceg-Hurn, Hill, Campbell, & McEvoy, 2021). The third study found responses of 33 people treated in a virtual day program to be indistinguishable from those of 60 people treated in a comparable in-person day program run prior to the COVID-19 outbreak (Levinson, Spoor, Keshishian, & Pruitt, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…Two of these, both uncontrolled, documented promising pre–post symptom changes in small groups ( n = 9 and n = 25, respectively) receiving routine treatments that were adapted to virtual formats (Plumley, Kristensen, & Jenkins, 2021; Raykos, Erceg‐Hurn, Hill, Campbell, & McEvoy, 2021). The third study found responses of 33 people treated in a virtual day program to be indistinguishable from those of 60 people treated in a comparable in‐person day program run prior to the COVID‐19 outbreak (Levinson, Spoor, Keshishian, & Pruitt, 2021). Here, we report on findings from a study comparing responses of patients who, following the COVID‐19 outbreak, received a virtual adaptation of a routine outpatient treatment “package” offered in a specialized ED program, to responses of a historical sample receiving the same treatment package in person prior to the outbreak.…”
Section: Introductionmentioning
confidence: 99%